Utilization of Public Open Space Area Facilities as an Alternative to Aerobic Dance Exercise (Department of Physical Education, Sport, Health and Recreation, 2023)
Sports in public open space areas is an option for now. This study aims to analyze the use of public open space areas as an alternative place to do aerobic dance exercise in the city of Makassar, South Sulawesi. This study uses a questionnaire given to active sports actors in public open space areas. The research subjects totaled 138 respondents with an age range of 13-55 years. This questionnaire was distributed in five public open space locations Car Free Day (CFD) Boulevard, Taman Pakui Sayang, Taman Macan, Karebosi, and Central Point Indonesia (CPI). This research was conducted for 3 weeks. The data obtained was analyzed by percentage. The results of the study show that most respondents are those who use public open space in Karebosi with a total of 47 respondents or 29%. The age of the majority of respondents was adolescent (17-25 years) as many as 117 respondents or 85%, jogging was still the most popular sport with 84 or 61% of respondents, while the aerobic dance was ranked second with 24 or 61% of respondents, 66 respondents. or 48% do sports with a frequency of 3-4 exercises per week, with a duration of 41-60 minutes per exercise carried out by 44 respondents or 32%. This states that sports carried out in public open space areas are an option for doing sports well and are in great demand by the people of the city of Makassar, South Sulawesi.